2004
DOI: 10.1007/s00432-004-0641-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary multifocal osseous Hodgkin disease: a case report and review of the literature

Abstract: Reviewing the few reported cases, osseous HD must be distinguished from systemic HD with diffuse bone marrow involvement and from osseous metastases in advanced stage of disease because it seems to have a better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…To the best of our knowledge, only 25 cases of primary bone HL involving either single or multiple bones have been reported in the literature [6,7].…”
Section: Introductionmentioning
confidence: 97%
“…To the best of our knowledge, only 25 cases of primary bone HL involving either single or multiple bones have been reported in the literature [6,7].…”
Section: Introductionmentioning
confidence: 97%
“…[8] In recent years, with combined modality treatments (radioand chemotherapy) the long term prognosis of patients with osseous HD appears good. [7,9] The use of surgery is restricted to obtaining open biopsies or treating mechanical or neurological complications. [4] CONCLUSION Although extremely rare, the primary osseous Hodgkin's lymphoma should be remember in the differential diagnosis of lytic lesions, especially involving the pelvis bones and vertebrae.The practical interest is to make early diagnosis because POHL have more favorable prognosis compared with other malignant bone lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Extranodal involvement is much less common in HL than in non-HL [8][9][10]. In this retrospective study of 384 newly diagnosed HL cases, extralymphatic disease was diagnosed in 19% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…PET/CT scanning has emerged as an important tool in the staging of patients with HL, and this adds significantly to the staging information obtained using other standard radiographic methods [4,5]. In the diagnosis and management of HL, 18F-fluorodeoxyglucose PET/CT is a functional imaging modality that has become a standard tool complementing contrastenhanced CT scans [9][10][11][12]. Several studies have shown that PET/CT helps to make a more accurate identification of the correct pretreatment stage in HL compared with contrast-enhanced CT, although PET/CT upstages disease from an early to an advanced stage in only 10-15% of patients whose treatment ultimately undergoes modification [4,5].…”
Section: Discussionmentioning
confidence: 99%